Prediction of air pollution from motor transport on city streets and districts - Rusakova, T. I. (Science and Transport Progress, 2013)
Purpose. Development of applied numerical model for prediction of atmospheric pollution rate on streets and districts of a city taking into account chemical transformations of pollutants. Methodology. To solve hydrodynamic task of determining velocity field of wind flow in street the method of discrete vortices was used, in the city district – the method of separation flows vortex of ideal incompressible fluid, for solution equation of pollutant transfer - alternating triangular implicit difference scheme. Findings.An efficient numerical model using the type of «street canyons»for prediction of air quality on city streets and districts with emissions from motor transport considering chemical transformations of pollutants was designed in the work. Originality.The numerical model, which allows taking into account impact of buildings on pollutants dispersion and requiring a small consumption of computer time during practical realization was created. The advantage of the model is the possibility of rapid calculation of emissions dispersion in the street with considering the chemical reactions of pollutants. Practical value. The developed numerical model can be used in practice during the planning of new highways in new urban areas or in the renovation of old ones, for a series of calculations that require search of different variants for arrangement of buildings, highways, under certain weather conditions.